The Influence of Entrepreneurial Education on Entrepreneurial Interest Among Students Mediated by Social Media - Agustin, Diana; Sulistyowati, Raya (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: As the population increases, it will create new problems in Indonesia. Purpose: This research aims to determine the effect of entrepreneurial education on entrepreneurial interest among students, mediated by social media. Novelty: social media as a mediating variable between entrepreneurial education and entrepreneurial interest Research Methods: This research uses a quantitative method with purposive sampling technique. The population in this study consists of students from the Faculty of Economics and Business at Surabaya State University, specifically from the Study Programs of Economic Education, Accounting Education, Office Administration Education, and Business Education, with a research sample of 232 respondents. Data analysis techniques using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the Smart-PLS4 tool. The testing model in this study includes outer model testing, inner model testing, and hypothesis testing. Results: The research results indicate that: (1) entrepreneurial education has a positive and significant effect on entrepreneurial interest, (2) entrepreneurial education has a positive and significant effect on social media, (3) social media has an insignifikcant effect in mediating the relationship between entrepreneurial education and entrepreneurial interest, this the third hypothesis is rejected. Research Contributions: The research results are expected to serve as a reference for future studies and can be developed on a broader scale